1993
DOI: 10.1037/0021-9010.78.4.662
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study on the early development of leader-member exchanges.

Abstract: The authors investigated the first 6 months that 166 newly hired employees and their immediate supervisors worked together. Expectations, perceived similarity, liking, demographic similarity, and performance were examined as determinants of leader-member exchanges (LMXs). Leader and member expectations of each other assessed in the first 5 days in the life of the dyad predicted LMXs at 2 weeks and at 6 weeks following the 1st day of the dyads' existence. Member expectations of leaders also predicted LMXs at 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
847
1
10

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 949 publications
(918 citation statements)
references
References 60 publications
37
847
1
10
Order By: Relevance
“…Since task performance is the traditional and primary focus of work exchange relationships, we propose a positive relationship between LMX and task performance. Consistent with this, Gerstner and Day's (1997) meta-analysis and other studies (e.g., Bauer, Erdogan, Liden, & Wayne, 2006;Klein & Kim, 1998;Liden, Wayne, & Stilwell, 1993) have demonstrated positive relationships between LMX and task performance. Thus, H3a: LMX will be positively related to task performance.…”
Section: Social Exchange Relationships: Leader-member Vs Team-membersupporting
confidence: 61%
“…Since task performance is the traditional and primary focus of work exchange relationships, we propose a positive relationship between LMX and task performance. Consistent with this, Gerstner and Day's (1997) meta-analysis and other studies (e.g., Bauer, Erdogan, Liden, & Wayne, 2006;Klein & Kim, 1998;Liden, Wayne, & Stilwell, 1993) have demonstrated positive relationships between LMX and task performance. Thus, H3a: LMX will be positively related to task performance.…”
Section: Social Exchange Relationships: Leader-member Vs Team-membersupporting
confidence: 61%
“…This is particularly pertinent to the study of leadership as research has shown the importance of liking in the early stages of leader-follower relationship development and its role as a precursor of leadership ratings (Engle & Lord, 1997;Lewter & Lord, 1992;Liden, Wayne, & Stilwell, 1993;Wayne & Ferris, 1990). Liden et al (1993), for instance, showed that liking assessed during the first two weeks of a leader-follower relationship predicted followers' ratings of the relationship six months later. This suggests that the initial basis for attitudinal evaluations can affect the interpretation of future attitude-relevant information.…”
Section: Relationship Between Affective and Cognitive Componentsmentioning
confidence: 99%
“…Again such findings have implications for leadership as it suggests that the way leaders try to persuade followers should match the content of the follower's attitude. It is clear that liking plays a powerful role in the early development of leader-follower relationships (Liden et al, 1993) and it is probable that for many followers leader-follower attitudes may be based on affect. In such cases leaders may be more persuasive if they make persuasive appeals rather than rational, cognitively-based appeals.…”
Section: Resistance To Counter-attitudinal Persuasionmentioning
confidence: 99%
See 2 more Smart Citations